Impact of Heat Pump-Driven Liquid Desiccant Dehumidification on the Energy Performance of an Evaporative Cooling-Assisted Air Conditioning System - Jang-Hoon Shin; Joon-Young Park; Min-Suk Jo; Jae-Weon Jeong (Energies, 2018)
The main objective of this research is to investigate the energy performance enhancement obtained by applying a heat pump to a liquid desiccant and indirect and direct evaporative cooling-assisted 100% outdoor air system (LD-IDECOAS). In conventional LD-IDECOAS operation, the boiler providing regeneration heat to the weak desiccant solution consumes most of the energy. In order to reduce the regeneration energy consumption in the LD-IDECOAS, a heat pump-integrated LD-IDECOAS (HPLD-IDECOAS) is suggested in this research. The heat pump reclaims waste heat from the absorber side of the system, and delivers the reclaimed heat to the regenerator side. Detailed energy simulations for both the LD-IDECOAS and HPLD-IDECOAS were conducted to analyze the energy saving potentiality of the proposed system over the conventional LD-IDECOAS. In both systems, it was assumed that a packed-bed type liquid desiccant unit with an aqueous solution of lithium chloride (LiCl) was used. In the proposed system, a heat pump with R-134a refrigerant was adopted. The results show that the proposed system was able to provide a 33% reduction in annual primary energy consumption compared with the conventional LD-IDECOAS. This significantly enhanced energy performance was mainly obtained through an 83% reduction in the gas energy consumed for regeneration of the desiccant solution in the proposed system by applying the heat pump.